Relationships between structure, ionization profile and sensitivity of exogenous anabolic steroids under electrospray ionization and analysis in human urine using liquid chromatography–tandem mass spectrometry. (16th September 2015) - Cha, Eunju; Kim, Sohee; Kim, Hee Won; Lee, Kang Mi; Kim, Ho Jun; Kwon, Oh‐Seung; Lee, Jaeick
Abstract: The relationships between the ionization profile, sensitivity, and structures of 64 exogenous anabolic steroids (groups I–IV) was investigated under electrospray ionization (ESI) conditions. The target analytes were ionized as [M + H] + or [M + H–nH2 O] + in the positive mode, and these ions were used as precursor ions for selected reaction monitoring analysis. The collision energy and Q3 ions were optimized based on the sensitivity and selectivity. The limits of detection (LODs) were 0.05–20 ng/mL for the 64 steroids. The LODs for 38 compounds, 14 compounds and 12 compounds were in the range of 0.05–1, 2–5 and 10–20 ng/mL, respectively. Steroids including the conjugated keto‐functional group at C3 showed good proton affinity and stability, and generated the [M + H] + ion as the most abundant precursor ion. In addition, the LODs of steroids using the [M + H] + ion as the precursor ion were mostly distributed at low concentrations. In contrast, steroids containing conjugated/unconjugated hydroxyl functional groups at C3 generated [M + H − H2 O] + or [M + H − 2H2 O] + ions, and these steroids showed relatively high LODs owing to poor stability and multiple ion formation. An LC‐MS/MS method based on the present ionization profile was developed and validated for the determination of 78 steroids (groups I–V) in human urine. Copyright © 2015 John Wiley & Sons, Ltd.